2015
DOI: 10.1158/0008-5472.can-14-3521
|View full text |Cite
|
Sign up to set email alerts
|

PML/RARα-Regulated miR-181a/b Cluster Targets the Tumor Suppressor RASSF1A in Acute Promyelocytic Leukemia

Abstract: In acute promyelocytic leukemia (APL), all-trans-retinoic acid (ATRA) treatment induces granulocytic maturation and complete remission of leukemia. MicroRNAs are known to be critical players in the formation of the leukemic phenotype. In this study, we report downregulation of the miR-181a/b gene cluster in APL blasts and NB4 leukemia cells upon ATRA treatment as key event in the drug response. We found that miR-181a/b expression was activated by the PML/RARα oncogene in cells and transgenic knock-in mice, an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 50 publications
(65 reference statements)
4
30
0
Order By: Relevance
“…Functional study had shown a decreased level of RSSF1A protein in NB4 cell line that was transfected with miR-181b. However, these data were unpublished data [8]. Consistent with this study, this miRNA was also found to be upregulated in gastric cancer cells and primary gastric cancer tissue [53].…”
Section: New Journal Of Sciencesupporting
confidence: 85%
See 1 more Smart Citation
“…Functional study had shown a decreased level of RSSF1A protein in NB4 cell line that was transfected with miR-181b. However, these data were unpublished data [8]. Consistent with this study, this miRNA was also found to be upregulated in gastric cancer cells and primary gastric cancer tissue [53].…”
Section: New Journal Of Sciencesupporting
confidence: 85%
“…Median survival for S-form was 19.9 months while all patients with L/V-form have survived to date [6]. Recent studies have reported that microRNAs (miRNAs) also play critical roles in the pathogenesis of APL, since miRNAs with oncogenic and tumour suppressor activity have been identified [7][8][9][10][11]. Discovery of miRNAs has opened up the possible application in molecular diagnostics and markers for follow up in patients with APL.…”
Section: Introductionmentioning
confidence: 99%
“…While certain microRNAs can act as either tumor suppressors or oncogenes in different tissues, the observation of contradictory functions of a single microRNA in the same tissue and even the same cell type is rare and unusual. Looking at the myeloid lineage in the hematopoietic system, miR-181a is such a candidate: while Hickey et al postulated its tumor-suppressive function in acute myeloid leukemia (AML) [4], several other groups revealed the oncogenic potential of miR-181a in the myeloid background [5, 6]. …”
mentioning
confidence: 99%
“…The mechanisms of cancer-related elimination or reduction of tumor suppressor proteins include transcriptional repression of the genes, degradation of proteins, and posttranslational modifications that change biological activities of these proteins (1,3,4). A number of recent papers showed that certain proteins work as oncoproteins and as tumor suppressors depending on cell environment, target genes, and posttranslational modifications (5)(6)(7)(8)(9)(10)(11)(12). In this regard, Dreijerink et al have recently shown that menin tumor suppressor protein displays its tumor suppression activity in a variety of cancer cells; however, it possesses oncogenic activities in breast tumorigenesis (5).…”
mentioning
confidence: 99%
“…Hickey et al recently demon-strated that microRNA 181a (miRNA181a) is upregulated by the C/EBP␣ 30-kDa protein and functions as a tumor suppressor in the hematopoietic system (7). However, later studies demonstrated that this miRNA also has oncogenic activities in the myeloid background (8,9). Similar to miRNA181a, miRNA22 first was shown to display oncogenic activity (10), but further studies in several tissue culture systems and in vivo clearly demonstrated its tumor suppressor activities (11,12).…”
mentioning
confidence: 99%